Predictive Analytics for Optimal Water Management in Smart Irrigation Systems Using Node-MCU Data (International Journal of Food and Nutritional Sciences, 2023)
Water management is a crucial aspect of modern agriculture, and the adoption of smart irrigationsystems has gained significant attention due to its potential to optimize water usage while maximizingcrop yields.